Balanced scorecard-based performance evaluation of Chinese county hospitals in underdeveloped areas. Issue 5 (May 2018) - Gao, Hongda; Chen, He; Feng, Jun; Qin, Xianjing; Wang, Xuan; Liang, Shenglin; Zhao, Jinmin; Feng, Qiming
Objective: Since the Guangxi government implemented public county hospital reform in 2009, there have been no studies of county hospitals in this underdeveloped area of China. This study aimed to establish an evaluation indicator system for Guangxi county hospitals and to generate recommendations for hospital development and policymaking. Methods: A performance evaluation indicator system was developed based on balanced scorecard theory. Opinions were elicited from 25 experts from administrative units, universities and hospitals and the Delphi method was used to modify the performance indicators. The indicator system and the Topsis method were used to evaluate the performance of five county hospitals randomly selected from the same batch of 2015 Guangxi reform pilots. Results: There were 4 first-level indicators, 9 second-level indicators and 36 third-level indicators in the final performance evaluation indicator system that showed good consistency, validity and reliability. The performance rank of the hospitals was B > E > A > C > D. Conclusions: The performance evaluation indicator system established using the balanced scorecard is practical and scientific. Analysis of the results based on this indicator system identified several factors affecting hospital performance, such as resource utilisation efficiency, medical service price, personnel structure and doctor–patient relationships.